The RMB in the global economy - Cheung, Yin-Wong (Cambridge : Cambridge University Press, 2022)
This Element discusses the global role of the RMB. After recapitulating its economic and trade growth experiences, we recount China's evolving exchange rate policy in the post-reform era, review the debate over whether the RMB is overvalued or undervalued, present China's policies to globalize the RMB, describe offshore RMB trading, assess the current global status of the RMB, and discuss geopolitical tensions in the last few years. Since 2009, the process of globalizing RMB has not been smooth sailing and progressed quite unevenly over time. Despite the strong performance in the early 2010s, the RMB is under-represented in the global market and its global role does not match China's economic might. The path of RMB internationalization is affected by both China's economic performance and geopolitical factors.
Introduction -- Background -- RMB Misalignment -- RMB Internationalization -- Current Status -- Geopolitics -- Concluding Remarks.
Title from publisher's bibliographic system (viewed on 09 Nov 2022).
Keywords: Renminbi; Foreign exchange -- China